Design and Archaeology for the Communication of Tangible and Intangible Content Between Real and Digital - Maria Laura Nappi; Elena Laudante; Mario Buono (DIID)
In the digital transition scenario, a new culture emerges in which the humanities and scientific disciplines merge and are sometimes contiguous and overlap in terms of expertise, thus opening new lines of research that are strongly interdisciplinary. In the complex process of archaeological research, innovative digital tools define new ways of communicating archaeological contexts through the synergy of technologies, languages and creativity. The paper highlights the dialogue between design and archaeology with reference to the relationship between past and present in the physical-digital space of fruition. In this regard, a reflection on the representation and interpretation of the fragmented nature of archaeological knowledge and the restitution of invisible contexts, artifacts and processes is proposed. This is to foster new configurations by linking physically inaccessible real spaces to usable virtual environments that are enduring over time.